Transcriptional control of ROS homeostasis by KUODA1 regulates cell expansion during leaf development - Lu, Dandan (Nature Pub. Group, 2014)
The final size of an organism, or of single organs within an organism, depends on an intricate coordination of cell proliferation and cell expansion. Although organism size is of fundamental importance, the molecular and genetic mechanisms that control it remain far from understood. Here we identify a transcription factor, KUODA1 (KUA1), which specifically controls cell expansion during leaf development in Arabidopsis thaliana. We show that KUA1 expression is circadian regulated and depends on an intact clock. Furthermore, KUA1 directly represses the expression of a set of genes encoding for peroxidases that control reactive oxygen species (ROS) homeostasis in the apoplast. Disruption of KUA1 results in increased peroxidase activity and smaller leaf cells. Chemical or genetic interference with the ROS balance or peroxidase activity affects cell size in a manner consistent with the identified KUA1 function. Thus, KUA1 modulates leaf cell expansion and final organ size by controlling ROS homeostasis.